Analisis Putusan Bebas terhadap Tindak Pidana Pemeliharaan Satwa yang Dilindungi (Studi Putusan Nomor 809/Pid.Sus/2024/Pn Dps) - Pratama, M. Ilham Wira (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2025)
The Panel of Judges at the Denpasar District Court through Decision Number 809/Pid.Sus/2024/Pn Dps issued a verdict of acquittal from all charges (vrijspraak) against the defendant who was charged with Article 21 paragraph (2) letter a in conjunction with Article 40 paragraph (2) of the KSDA-HE Law for the possession of four Javan Porcupines (Hystrix Javanica) which are protected animals, due to the failure to fulfill the element of "intention" in committing a crime related to the defendant's ignorance that the Javan porcupine is a protected animal. Therefore, this decision needs to be studied, especially regarding the considerations of the Panel of Judges in issuing the acquittal verdict. The research method used in this research is the normative legal research method, using three research approaches, namely the statute approach, the conceptual approach, and the case approach, and the analysis technique used is qualitative prescriptive. The results of the study concluded that the Panel of Judges did not have strong and adequate arguments in their considerations in issuing a verdict of acquittal (vrijspraak) against the defendant and disregarded legal certainty due to their error in applying Article 21 paragraph (2) letter a of the KSDA-HE Law as the basis for the indictment.